"Guilty with explanation": rethinking the destiny of landfills in a Millennium City in Ghana. Issue 2 (4th March 2014) - Oteng-Ababio, Martin
Abstract : Purpose: – The purpose of this paper is to interrogate the fate of landfills as waste disposal option in Accra. This becomes imperative since for a long time, efficient disposal of waste remains a neglected issue and potential source environmental hazard. Design/methodology/approach: – The study adopted content analysis of literature, in-depth interview schedules with key stakeholders and direct field observations. Findings: – Landfills in Accra are in a state of ambivalence due to mismanagement. Improper designing and siting of dumpsites, often in close proximity to water sources and human settlements have created aesthetic and odour nuisances and increase health risks, attracting the wrath, disaffection and distrust of residents. Research limitations/implications: – The study provides an insight into broader issues of landfills and demonstrates Accra's vulnerability to health hazard due to improper waste disposal, which becomes apparent with the least downpour and the subsequent flooding which exposes most drains as de facto receptacles for waste. Practical implications: – From all indications, Accra appears to be on the brink of a landfill void. Though this issue has been an open secret since 2000, it remains unattended to till date and calls for an immediate, well-planned and concerted attention. Originality/value: – This paper adopts qualitative research techniques to delve into a subject matter whose implication has citywide consequences. The method allows for in-depth assessment of the intent and commitment of all key stakeholders, which brings to the fore that landfills will no longer be the cheapest or simplest waste disposal option.